Method for reinforcing surface mineralization and hardening of large prefabricated part

By processing micropores on the template of large prefabricated components and spraying carbon dioxide gas into the surface, combined with vibration and autoclaving and maintenance, the problem of slow carbon dioxide diffusion in the existing technology is solved, and the rapid formation of dense mineralized layers is achieved, which improves the improvement of The resistance and durability of concrete.

CN119238719AActive Publication Date: 2025-01-03ANHUI CONCH IND TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411359941.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the prior art, carbon dioxide diffuses slowly in concrete, making it difficult to quickly form dense mineralized layers, resulting in low mineralization efficiency and difficult to meet the requirements of large components to resist permeability, frost resistance and corrosion resistance.

Method used

Process micropores on steel formwork of large prefabricated components, spray high-purity carbon dioxide gas into the concrete surface through the micropores, and mineralization reactions are carried out during the process of decompression and autoclaving, combining the spraying and autoclaving of surface enhancer and the maintenance of autoclaving. , control the depth and flow of carbon dioxide injection to form a dense mineralized layer.

Benefits of technology

Accelerate concrete hardening, improve strength and density, enhance the durability of components, reduce the erosion of harmful ions, shorten the production cycle, and increase the thickness and density of the mineralized layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119238719A_ABST
    Figure CN119238719A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of prefabricated part production, and discloses a large prefabricated part surface mineralization hardening enhancing method which comprises the following steps: step 1, processing a plurality of micropores in a steel template for pouring a large prefabricated part, uniformly arranging the micropores in the steel template, and assembling a mold by using the processed steel template; and 2, steel bars are bound and then fixed in a mold, the poured concrete and the mold are arranged on a vibration table together and are compacted through the vibration table, and carbon dioxide gas is sprayed into the surface layer of the concrete. And thirdly, after compaction, the large prefabricated part is subjected to standard curing or steam curing with a mold. And 4, spraying a surface reinforcing agent liquid on the surface of the large prefabricated part, and then performing mineralization reaction in a still kettle. And 5, the autoclaved large prefabricated part is immersed in saturated lime water to be cured to a certain age. The carbonization uniformity of surface concrete is improved, and the formation efficiency of a carbonization layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of prefabricated component production, and in particular relates to a method for strengthening the surface mineralization hardening of a large prefabricated component. Background Art

[0002] Large prefabricated components mostly use reinforced concrete structures. Concrete itself is alkaline, which can form a passivation layer on the surface of the steel bars, thereby preventing the steel bars from rusting. In order to accelerate the hardening of concrete, increase its strength, and fix carbon dioxide during the production process, mineralization technology is generally used to mineralize the concrete to a certain extent. The mineralization process will cause the alkalinity of the concrete to decrease, which increases the risk of steel corrosion to a certain extent. Therefore, it is necessary to enhance the surface of the concrete component during the mineralization process and increase the density of the mineralized layer, so as to slow down the intrusion of harmful ions during the service of the component and ensure the durability of the reinforced concrete.

[0003] At present, in the prior art, most of them are to fill carbon dioxide into the space where the component is located during the curing process so that the concrete surface contacts with carbon dioxide to produce a mineralization reaction. Some technologies drill holes on the mold surface, and then spray carbonated water or calcium bicarbonate solution on the permeable template cloth, cover the permeable template cloth on the mold surface, and let the component surface react with the liquid on the permeable template cloth to achieve mineralization, while the outside is filled with carbon dioxide to supplement the solution on the permeable template cloth with carbon dioxide. However, the above-mentioned prior art is to allow carbon dioxide to contact only the surface of the component, gradually infiltrate the outside of the component to react and form a mineralized layer. Therefore, the diffusion rate of carbon dioxide in concrete is slow, and in a static state, a carbonate film layer will form on the surface of the component, further hindering the infiltration of carbon dioxide. Therefore, the prior art not only has a low mineralization efficiency, but also is difficult to form a thicker mineralized layer, generally 0.5-6mm. If large components have higher requirements for impermeability, frost resistance and corrosion resistance, the prior art is difficult to quickly form a thicker dense mineralized layer, and the carbon fixation efficiency is also very low. Summary of the invention

[0004] The purpose of the present invention is to provide a method for enhancing the surface mineralization and hardening of large prefabricated components, which is used to solve the technical problem in the prior art that it is difficult to achieve a high mineralization efficiency due to the slow diffusion of carbon dioxide in concrete, especially it is difficult to quickly form a dense mineralized layer with a certain depth on the concrete surface.

[0005] The method for enhancing the surface mineralization hardening of large prefabricated components comprises the following steps.

[0006] Step 1: Process a number of micro holes on a steel formwork used for casting large prefabricated components. The micro holes are evenly arranged on the steel formwork, and the processed steel formwork is used to assemble the formwork; a storage container for high-purity compressed carbon dioxide gas is set on the other side, and a pipeline system is set up to connect the outlet of the storage container in parallel with a number of gas nozzles. The gas nozzles are installed one by one in the micro holes so that they can spray gas to the inside of the formwork.

[0007] Step 2: After the steel bars are tied, they are fixed in the mold, and the distance between the steel bars and the steel formwork is not less than the required concrete protective layer thickness. The mixed concrete is then poured into the mold. The poured concrete and the mold are placed on a vibration table and compacted by the vibration table. During the compaction process, high-purity carbon dioxide gas is sprayed into the surface of the concrete through the micropores through the gas nozzle.

[0008] Step 3: After compaction, the large prefabricated components are subjected to standard curing or steam curing with molds.

[0009] Step 4: After the curing is completed, the mold of the large prefabricated component is removed, the surface of the large prefabricated component is sprayed with a surface enhancer liquid, and then the large prefabricated component is transferred to an autoclave for autoclave curing, and a mineralizing gas is introduced into the autoclave for a mineralization reaction.

[0010] Step 5: After the autoclaving is completed, the large prefabricated components are immersed in saturated lime water or clean water for curing to a certain age.

[0011] Preferably, in step 1, the diameter of the micropores is 0.01 to 5 mm, the micropore spacing is 50 to 200 mm, and a gas flow controller is provided on the pipeline system to control the flow of each gas nozzle. After being controlled, the compressed carbon dioxide pressure output is 0 to 1 MPa.

[0012] Preferably, in step 2, the distance between the steel bar and the template is 10 to 100 mm, and the injection depth of the carbon dioxide gas is 2 to 90 mm.

[0013] Preferably, in step 2, the injection depth of the carbon dioxide gas is controlled by a gas flow controller, and mineralization is performed by intermittently injecting carbon dioxide gas.

[0014] Preferably, in step 4, tail gas containing carbon dioxide discharged from a cement plant is used as the mineralizing gas; and in this step, the surface enhancement liquid is sprayed multiple times in the autoclave to enhance the mineralization degree of the prefabricated part surface.

[0015] Preferably, the surface enhancer includes a surface hardener, silicone and a mineralizer. The surface enhancer is sprayed as follows: first spray the silicone once, then spray the mineralizer several times, and finally spray the surface hardener once. The spraying amount of each component is calculated by mass fraction, which is 0.5 to 15 parts of the surface hardener, 0.05 to 10 parts of the silicone, and 99.45 to 75 parts of the mineralizer.

[0016] Preferably, the organic silicon includes at least one of dimethyl silicone oil, polydimethylsiloxane and polyether-siloxane copolymer.

[0017] Preferably, the surface hardener includes at least one of magnesium fluorosilicate, aluminum fluorosilicate, and lithium silicate.

[0018] Preferably, the mineralizer includes at least one of a saturated calcium hydroxide solution, a saturated magnesium hydroxide solution, a steel slag leachate, and a magnesium chloride solution.

[0019] The present invention has the following advantages: 1. In the process of compaction, pure carbon dioxide is sprayed into the surface concrete through micropores. After the surface concrete reacts with carbon dioxide, hardening can be accelerated and strength can be improved, thereby achieving the effect of accelerating demoulding, improving demoulding quality, and shortening the production cycle. This solution can control the single injection amount of carbon dioxide by intermittent injection. The injected pure carbon dioxide is completely absorbed after reaction and will not cause a large number of pores in the concrete. Carbonization after hardening of concrete will cause the volume of solid minerals in the microstructure of concrete to shrink, thereby affecting the density and strength of the concrete, while this will not happen with carbonization of freshly mixed concrete.

[0020] 2. Carbon dioxide is sprayed into the concrete during compaction. The carbon dioxide bubbles are evenly dispersed within a certain range during the violent vibration, which is beneficial to improve the carbonization uniformity of the surface concrete and improve the efficiency of carbonization layer formation.

[0021] 3. This solution uses a gas flow controller to control the depth of carbon dioxide spraying into the concrete surface. Carbon dioxide only reacts with the freshly mixed concrete on the surface, and does not affect the alkalinity around the internal steel bars. Moreover, the surface concrete after carbonization is more compact, composed of stable, non-reactive calcium carbonate and silicon dioxide, which reduces the erosion of other ions such as sulfate ions and chloride ions, thereby improving the durability of reinforced concrete.

[0022] 4. The autoclave uses cement kiln tail gas and waste heat to reduce the energy consumption of steam curing. Repeated spraying of surface enhancement liquid further absorbs carbon dioxide and generates mineral components, thereby filling the holes and cracks on the surface, continuously enhancing the density of the specimen surface and improving the durability of the prefabricated components. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1It is a schematic diagram of step 2 in the method for strengthening the surface mineralization and hardening of large prefabricated components of the present invention.

[0024] Figure 2 It is a schematic diagram of the mold in the surface mineralization hardening enhancement method of large prefabricated components of the present invention.

[0025] The reference numerals in the accompanying drawings include: 1. mold, 11. steel template, 12. gas nozzle, 2. pipeline system, 3. gas flow controller, 4. storage container. DETAILED DESCRIPTION

[0026] The specific implementation modes of the present invention are further explained in detail below by describing the embodiments with reference to the accompanying drawings, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.

[0027] like Figure 1 , Figure 2 As shown, the present invention provides a method for strengthening the surface mineralization hardening of large prefabricated components, comprising the following steps.

[0028] Step 1: Process a number of micropores on a steel template 11 used for casting large prefabricated components. The micropores are evenly arranged on the steel template 11, and the processed steel template 11 is used to assemble the mold; a storage container 4 for high-purity compressed carbon dioxide gas is set on the other side, and a pipeline system 2 is set to connect the outlet of the storage container 4 in parallel with a number of gas nozzles 12. The gas nozzles 12 are installed in the micropores one by one so that they can spray gas to the inside of the template.

[0029] In this step, the diameter of the micropores is 0.01-5 mm, the micropore spacing is 50-200 mm, and a gas flow controller 3 is provided on the pipeline system 2 to control the flow of each gas nozzle 12. The pressure of the compressed carbon dioxide output after control is 0-1 MPa.

[0030] Step 2: After the steel bars are tied, they are fixed in the mold 1, and the distance between the steel bars and the steel formwork 11 is not less than the required concrete protective layer thickness, and then the mixed cement concrete is poured into the mold 1, and the poured concrete and the mold 1 are placed on a vibration table and compacted by the vibration table. During the compaction process, high-purity carbon dioxide gas is sprayed into the surface of the concrete through the micropores through the gas nozzle 12.

[0031] The dense mineralized concrete layer can prevent harmful ions in the environment from entering the concrete, and the sufficient alkaline concrete thickness can avoid the failure of the protective effect of the steel bars. Therefore, the thickness of the concrete protective layer is equal to the sum of the thickness of the mineralized layer and the sufficient alkaline concrete thickness around the steel bars. The sufficient protective layer thickness can ensure the good corrosion resistance of the steel bars under actual service conditions. In this embodiment, according to the needs of large prefabricated components, the distance between the steel bars and the template is 10 to 100 mm, and the injection depth of the carbon dioxide gas is 2 to 90 mm. The injection depth of the carbon dioxide gas is controlled by the gas flow controller 3, and the mineralization is carried out by intermittent injection of carbon dioxide gas.

[0032] Step 3: After compaction, the large prefabricated components are subjected to standard curing or steam curing with molds.

[0033] Step 4: After the curing is completed, the mold 1 of the large prefabricated component is removed, and the surface enhancer liquid is sprayed on the surface of the large prefabricated component. Then, the large prefabricated component is transferred to an autoclave for autoclave curing, and mineralizing gas is introduced into the autoclave for mineralization reaction.

[0034] This embodiment uses tail gas containing carbon dioxide discharged from a cement plant as the mineralizing gas; and in this step, the surface enhancement liquid is sprayed multiple times in the autoclave to enhance the mineralization degree of the prefabricated part surface.

[0035] The surface enhancer includes a surface hardener, silicone and a mineralizer. The surface enhancer is sprayed in the following manner: first spray the silicone once, then spray the mineralizer several times, and finally spray the surface hardener once. The spraying amount of each component is calculated by mass fraction, 0.5 to 15 parts of the surface hardener, 0.05 to 10 parts of the silicone, and 99.45 to 75 parts of the mineralizer. Among them, the silicone includes at least one of dimethyl silicone oil, polydimethylsiloxane and polyether-siloxane copolymer. The surface hardener includes at least one of magnesium fluorosilicate, aluminum fluorosilicate and lithium silicate. The mineralizer includes at least one of saturated calcium hydroxide solution, saturated magnesium hydroxide solution, steel slag leachate and magnesium chloride solution.

[0036] Step 5: After the autoclaving is completed, the large prefabricated components are immersed in saturated lime water or clean water for curing to a certain age.

[0037] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the inventive concept and technical solution of the present invention, or the inventive concept and technical solution are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for strengthening the surface mineralization hardening of large prefabricated components, characterized in that: The following steps are involved: Step 1: Processing a plurality of micro-holes on a steel template (11) for casting a large prefabricated component, wherein the micro-holes are evenly arranged on the steel template (11), and the processed steel template (11) is used to assemble a mold; a storage container (4) for high-purity compressed carbon dioxide gas is arranged on the other side, and a pipeline system (2) is arranged to connect the outlet of the storage container (4) in parallel with a plurality of gas nozzles (12), wherein the gas nozzles (12) are installed one by one in the micro-holes so as to spray gas to the inside of the template; Step 2: After the steel bars are tied, they are fixed in the mold (1), and the distance between the steel bars and the steel formwork (11) is not less than the required concrete protective layer thickness, and then the mixed concrete is poured into the mold (1), and the poured concrete and the mold (1) are placed on a vibration table and compacted by the vibration table. During the compaction process, high-purity carbon dioxide gas is sprayed into the surface of the concrete through the micropores through the gas nozzle (12); Step 3: After compaction, the large prefabricated components are subjected to standard curing or steam curing with molds; Step 4: After the curing is completed, the mold of the large prefabricated component (1) is removed, a surface enhancer liquid is sprayed on the surface of the large prefabricated component, and then the large prefabricated component is transferred to an autoclave for autoclave curing, and a mineralizing gas is introduced into the autoclave for a mineralization reaction; Step 5: After the autoclaving is completed, the large prefabricated components are immersed in saturated lime water or clean water for curing to a certain age.

2. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 1, characterized in that: In step 1, the diameter of the micropores is 0.01 to 5 mm, the micropore spacing is 50 to 200 mm, and a gas flow controller (3) is provided on the pipeline system (2) to control the flow of each gas nozzle (12). After being controlled, the compressed carbon dioxide pressure output is 0 to 1 MPa.

3. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 1, characterized in that: In step 2, the distance between the steel bar and the template is 10 to 100 mm, and the injection depth of the carbon dioxide gas is 2 to 90 mm.

4. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 1, characterized in that: In step 2, the injection depth of the carbon dioxide gas is controlled by a gas flow controller (3), and mineralization is performed by intermittently injecting carbon dioxide gas.

5. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 1, characterized in that: In step 4, the tail gas containing carbon dioxide discharged from the cement plant is used as the mineralizing gas; and in this step, the surface enhancement liquid is sprayed multiple times in the autoclave to enhance the mineralization degree of the prefabricated part surface.

6. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 1, characterized in that: The surface enhancer includes a surface hardener, silicone and a mineralizer. The surface enhancer is sprayed in the following manner: first spray the silicone once, then spray the mineralizer several times, and finally spray the surface hardener once. The spraying amount of each component is calculated by mass fraction, which is 0.5 to 15 parts of the surface hardener, 0.05 to 10 parts of the silicone, and 99.45 to 75 parts of the mineralizer.

7. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 6, characterized in that: The organic silicon includes at least one of dimethyl silicone oil, polydimethylsiloxane and polyether-siloxane copolymer.

8. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 6, characterized in that: The surface hardener includes at least one of magnesium fluorosilicate, aluminum fluorosilicate, and lithium silicate.

9. The method for strengthening the surface mineralization hardening of large prefabricated components according to claim 6, characterized in that: The mineralizer includes at least one of a saturated calcium hydroxide solution, a saturated magnesium hydroxide solution, a steel slag leaching solution, and a magnesium chloride solution.

Citation Information

Patent Citations

  • Preparation method of high anti-carbonization reinforced concrete

    CN109795020A

  • Carbon dioxide cured prefabricated water-permeable concrete and preparation method thereof

    CN109824321A

  • Carbon dioxide mineralization maintenance method for precast concrete component

    CN115536432A

  • Production process of precast concrete component for carbon dioxide curing

    CN116494368A